Extended Frontobasal Approach for Skull Base Lesions - Mohd Faheem; Raj Kumar; Hanuman Prasad Prajapati (Indian Journal of Neurosurgery)
Background Lesions involving the skull base can be approached by a variety of surgical corridors and extended frontobasal approach is one of them. It provides quite a wide exposure to lesions in the midline of anterior skull base, paranasal sinuses, and sphenoclival region. Objective To share our experience, and list the merits and demerits, of this approach for anterior skull base lesions. Methods A total of six cases were operated using extended frontobasal approach. Four of them were skull base tumors with extensive involvement of paranansal sinuses and extension into sellar, parasellar, and clival region. Fronto-orbital and sphenoethmoidal osteotomy provided adequate surgical access, thereby facilitating their excision. Two cases of frontonaso-orbital encephalocele with large bone defect at anterior skull base were also operated upon. Skull base repair was performed using autologous bone graft, pericranium, and fibrin glue. Results  Gross total excision was achieved in four cases of skull base tumors with good cosmesis as transfacial access was obviated. Excision, repair, and reconstruction of two patients with frontonaso-orbital encephalocele were also done with acceptable cosmesis. Conclusion The extended frontobasal approach is an excellent alternative for extensive anterior skull base tumors (up to posterior skull base), and also for the repair of large malformative lesions of the anterior skull base.